TUNTUTAN KERJA PRAMUWISATA BERBAHASA JERMAN DALAM ERA GLOBALISASI PADA BIRO PERJALANAN WISATA DI KABUPATEN BADUNG - Made Artajaya (Jurnal Ilmiah Hospitality Management, 2016)
Many new establishments of tour travel in Bali that their target market is tourists from Germany affecting a competitive business among those tour and travel agency. The impact is reducing amount of German tourists using the service of tour travel which directly affecting the intensity of work of Germany tour guide. Therefore, there is a demand for the tour guides who work at tour travel agency to work more professional to face the competitiveness among themselves. This research is aimed to describe and analyze the problem of demand of professional work by Germany tour guide who work at the tour travel establishment in Badung regency, in this global era. Some theories used to support this research such as the hegemony theory, social practical theory, and communicative act eclecticly theory. The demand for working professionally in this global era means of the need to force themselves as the Germany tour guide in completing their job. On the other hands, the tour guide should add their knowledge of Germany language, as well as knowledge of guiding.